ERROR EVALUATION OF EQUIVALENT CALCULATIONS ON ELECTRIC ENERGY LOSSES IN 6–20 KV POWER NETWORKS - M. I. Fursanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Algorithmic methodology has been developed to evaluate calculation errors of individual equivalent resistances of power lines and transformers of 6–20 kV power networks under operational conditions. Influence of load on electric energy losses in networks has been analyzed and it is shown that remoteness of a load (place of connection) from power supply source is the main factor effecting the losses.